home
***
CD-ROM
|
disk
|
FTP
|
other
***
search
/
Multimedia Algebra
/
Algebra1.iso
/
ALGEBRA1
/
CHAPTER5.5T
< prev
next >
Wrap
Text File
|
1994-02-15
|
9KB
|
303 lines
301
à 5.5ïForms of a Linear Equation
äïPlease write the following equations in standard form.
âè 3êê ┌ï3 ┐è3è ┌ï3 ┐êê┌ï3 ┐
#êx = -y - 4ï─¥ïx + │- -y│ = -y + │- -y│ - 4ï─¥ïx + │- -y│ = -4
êè 2êê └ï2 ┘è2è └ï2 ┘êê└ï2 ┘
êë ┌ï3 ┐
# ─¥ï2∙x + 2∙│- -y│ = 2(-4)ï─¥è 2x + (-3y) = -8è─¥è 2x - 3y = -8
êë └ï2 ┘
éS
Standard form for a linear equation in two variables is AX + BY = C.
Notice that the first term is the 'x' term, the second term is the 'y'
term, and the constant term 'C' is on the right side of the equal sign.
Also in standard form the coefficients A, B, C are not fractions.
Finally the coefficient 'A' is positive.ïIt should be noted that the
standard form varies from algebra book to algebra book.
êêêêê 3
In order to write the equationïx = -y - 4, in standard form, you should
move the 'y' term over by addingè 2èit to both sides of the equation
êêï┌ï3 ┐è3è ┌ï3 ┐êê 3
#êëx + │- -y│ = -y + │- -y│ -4 ─¥ëx - -y = -4
êêï└ï2 ┘è2è └ï2 ┘êê 2
Next, clear the fraction by multiplying both sides of the equation by 2.
êê ┌ï3 ┐
#ê2∙x + 2∙│- -y│ = 2(-4)è─¥êè 2x - 3y = -8
êê └ï2 ┘êêïThis is now in standard form.
1êèWriteïy = 2x + 5ïin standard form.
êêêêïyêêêêëå
ïA)ï2x - y = -5ëB)ïx - ─ = 5ë C)ï2x + y = 5ë D)ïof
êêêêï2êêêêëç
üêêêè y = 2x + 5
êêêè -2x + y = 2x + (-2x) + 5
êêêè -2x + y = 5
êêèMultiplying both sides by minus one gives
êêêë2x - y = -5
Ç A
2êèWriteï3y - 6 = 2xïin standard form.
ë 2êêêêêêêêèå
ïA)ï-x - y = -2ëB)ï3x - 2y = 6ëC)ï2x - 3y = -6ëD)ïof
ë 3êêêêêêêêèç
üêêêï3y - 6 = 2x
êêêï-2x + 3y - 6 = 2x + (-2x)
êêêï-2x + 3y - 6 = 0
êêë-2x + 3y + 6 - 6 = 0 + 6
êêêë -2x + 3y = 6
êêêê2x - 3y = -6
Ç C
3êêê 2è y
êêë Writeï6 - -x = ─èin standard form.
êêêêè3è 4
êêêêêêêêêèå
ïA)ï4x - 3y = 6ëB)ï8x + 3y = 72è C)ï3x + 4y = -6ëD)ïof
êêêêêêêêêèç
üë2è yêè 2è ┌ -2 ┐ë2è yêè 2è y
#ê6 - -x = ─ï─¥è6 + -x + │- -x│ï=ï-x + ─ï─¥è6 = -x + ─
êè 3è 4êè 3è └ï3 ┘ë3è 4êè 3è 4
êï2è yêë ┌ 2 ┐ë┌ y ┐
#è─¥è ─x + ─ = 6ï─¥è12│ -x│ + 12│ ─ │ = 12∙6è ─¥è8x + 3y = 72
êï3è 4êë └ 3 ┘ë└ 4 ┘
Ç B
äïPlease write an equation in slope-intercept form for the
êêline with the given slope and y-intercept.
âïWrite an equation in slope-intercept form for a line with
êïslope 3 and y-intercept (0,4).
êêêêïy = mx + b
êêêêïy = 3x + 4
éS
Slope-intercept form for a linear equation in two variables is
y = mx + b.ïIn this form 'y' is by itself on the left side of the
equation.ïThe 'x' term and the constant term are on the right.ïThe
coefficient, m, of x is always the slope and the number, b, is the
y-intercept.
In order to find an equation of the line with slope 3 and y-intercept
(0,4), you should start by writing down the slope-intercept formula.
êêêêïy = mx + b
Next substitute '3' in for 'm', and '4' in for 'b'.
êêêêïy = 3x + 4
4êêêêêêêêè 2
êè Write an equation in slope-intercept form for a line with ─
êè slope and y-intercept (0,-5).êêêê 3
êê 2êê2êê 2êêëå
ïA)ïy = 5x - ─ë B)ïy = -x - 5ë C)ï-x + 4y = 5ë D)ïof
êê 3êê3êê 3êêëç
üêêêèy = mx + b
êêêêë 2
êêêêïy = -x - 5
êêêêë 3
Ç B
5
êè Write an equation in slope-intercept form for a line with
êè slope -3 and y-intercept (0,5)
êêêêêêè 3êêëå
ïA)ïy = -3x + 5ëB)ï-3x - y = -5è C)ï-x + y = 5êD)ïof
êêêêêêè 2êêëç
üêêêèy = mx + b
êêêêïy = -3x + 5
Ç A
6
êè Write an equation in slope-intercept form for a line with
êè zero slope and y-intercept (0,-2).
êêêêêêêêêèå
ïA)ï2x + y = 1ë B)ïx + y = -2ê C)ïy = -2êïD)ïof
êêêêêêêêêèç
üêêêèy = mx + b
êêêêïy = 0∙x + (-2)
êêêêïy = -2
Ç C
äïPlease identify the slope and the y-intercept of the line
êêwith the given equation.
âêêê 2x + 2y = 6
êë2x + 2y = 6êêë2yè-2xè6
#è 2x + (-2x) + 2y = -2x + 6è ┌─¥ë ── = ─── + ─
êêè2y = -2x + 6è─┘êï2è 2è 2
êêêêêê y = -x + 3
éS
In order to find the slope and y-intercept of 2x + 2y = 6, you should
solve for y.
êêêê 2x + 2y = 6
êêê2x + (-2x) + 2y = -2x + 6
êêêêë 2y = -2x + 6
êêêêêy = -x + 3
This is the slope-intercept form.ïThe slope is m = -1 and the
y-intercept is (0,3).
7ïIdentify the slope and y-intercept of 2x + 3y = 12.
êêêêè2êêë 3êêå
ïA) m = 3ï(0,2)ëB) m = - -ï(0,4)ë C) m = ─ï(0,3)è D)ïof
êêêêè3êêë 2êêç
üï2x + 3y = 12êêï3yë2xè12êë 2
#2x + (-2x) + 3y = -2x + 12è ┌─¥è── = - ── + ──ï─¥èy = - -x + 4
êë 3y = -2x + 12è─┘ë 3ë 3è 3êë 3
êêêêë2
êêêë m = - ─èand (0,4)
êêêêë3
Ç B
8ïIdentify the slope and y-intercept of 3x - 4y = 6.
ê 3ê3êêêêêêê å
A) m = ─ï(0,- ─)ëB) m = 4ï(0,-3)ë C) m = 3ï(0,4)è D)ïof
ê 4ê2êêêêêêê ç
üï3x - 4y = 6êêï-4yè -3xè 6êë3è 3
#3x + (-3x) - 4y = -3x + 6ë┌─¥ï─── =ï─── + ──ï─¥èy =ï-x - ─
êë-4y = -3x + 6è ─┘ë-4ë-4è-4êë4è 2
êêêêè3êë 3
êêêë m = -è and (0,- ─)
êêêêè4êë 2
Ç A
9êIdentify the slope and y-intercept of y = -7.
êêêêêêêêêè å
ïA) m = 2ï(0,3)ëB) m = 1ï(0,7)ë C) m = 0ï(0,-7)ëD)ïof
êêêêêêêêêè ç
üêêêè y = -7
êë This is a horizontal line so the slope is m = 0
êêè and the y-intercept is (0,-7).
Ç C
äïPlease find an equation of the line passing through the
given point and slope.ïWrite the answer in standard form.
â Find the equation in standard form of a line having slope m = 2/3
#and passing through point (5,7).èy - y¬ = m(x - x¬)
êè 2
#èy - 7 = ─(x - 5)ê┌─¥êê3y - 21 = 2x - 10
êè 3êê│ë -2x + 3y -21 + 21 = 2x - 2x -10 + 21
êêêë│êê -2x + 3y = 11
è3(y - 7) = 2(x - 5)ï──┘êêï2x - 3y = -11
éS
#The point-slope formula for the equation of a line isïy - y¬ = m(x - x¬
êêêêêêêêï2
#Since the given point is (5,7) and the given slope is m = ─,ïx¬ is
#replaced by 5, and y¬ is replaced by 7 (Step 1).êè3
The fraction is cleared by multiplying both sides by 3 (Step 2) and then
distributive property is applied (Step 3).ïFinally like terms are
collected and the equation is left in standard form (Step 4).
Step 1êè 2êê Step 3ï3(y - 7) = 2(x - 5)
êïy - 7 = ─(x - 5)êêï3y - 21 = 2x - 10
êêè3
Step 2êê 2êè Step 4ï-2x + 3y = -10 + 21
ê 3(y - 7) = 3∙─(x - 5)êë-2x + 3y = 11
êêê3êêë 2x - 3y = -11
10ïFind the equation (in standard form) of the line that passes
through (-2,7) and has slopeë 3
êêêêïm = ─
êêêêë 4
êêêêêêêêêëå
A)ï2x - 7y = 9ëB)ï3x - 4y = -34ëC)ï3x + 9y = 11ë D)ïof
êêêêêêêêêëç
ü
#êêè 3êë ┌─¥ë 4(y - 7) = 3(x + 2)
êèy - 7 = ─(x - (-2))ï─┘êï4y - 28 = 3x + 6
êêè 4êêê -3x + 4y = 6 + 28
êêêêêë -3x + 4y = 34
êêêêêê3x - 4y = -34
Ç B
11ïFind the equation (in standard form) of the line that passes
through (3,-6) and has slopeê 4
êêêêïm = - ─
êêêêê 5
êêêêêêêêêè å
A) 4x + 5y = -18ëB)ï3x - 5y = 13ë C)ï2x + 4y = -8ëD)ïof
êêêêêêêêêè ç
ü
#êêë 4êë┌─¥ë 5(y + 6) = -4(x - 3)
êy - (-6) = - ─(x - 3)è ─┘êï5y + 30 = -4x + 12
êêë 5êêê 4x + 5y = 12 - 30
êêêêêê 4x + 5y = -18
Ç A
12ïFind the equation (in standard form) of the line that passes
through (-2,-3) and has slope zero.
êêêêêêêêêè å
A) x = -2êëB)ï2x + 3y = 1êC)ïy = -3êè D)ïof
êêêêêêêêêè ç
ü
êëThis is a horizontal line passing through (-2,-3)
êêëand so the equation is y = -3.
Ç C
äïPlease find the equation in standard form of the line
êêpassing through the given pair of points.
âïFind the equation of the line passing through (2,-4) and (1,7).
è 7 - (-4)è7 + 4è11êêëy - (-4) = -11(x - 2)
m = ──────── = ───── = ── = -11êêïy + 4 = -11x + 22
ë1 - 2ë -1ë-1êêï11x + y + 4 = 22
êêêêêêè11x + y = 22 - 4
êêêêêêè11x + y = 18
éS
In order to find the equation of the line passing through (2,-4) and
(1,7), it is first necessary to find the slope using the slope formula.
#êèy½ - y¬êêë 7 - (-4)è7 + 4è11
ë m = ───────êê mï= ──────── = ───── = ── = -11
#êèx½ - x¬êêê1 - 2ë -1ë-1
Then choose either of the given two points and substitute values into
the point-slope form.
êêêêêêëy - (-4) = -11(x - 2)
#èy - y¬ = m(x - x¬)êêêê y + 4 = -11x + 22
êêêêêêï11x + y + 4 = 22
êêêêêêë 11x + y = 22 - 4
êêë This is in standard formè 11x + y = 18
13ïFind the equation in standard form of the line passing
êëthrough (-4,2) and (1,3).
êêêêêêêêêïå
ïA)ïx - 5y = -14è B)ï4x - 2y = 6ëC)ïx + 3y = -4ëD)ïof
êêêêêêêêêïç
üêêê│êè 1
êêêë │èy - 3 = ─(x - 1)
ë3 - 2ê1ë1è│êè 5
m = ──────── = ───── = ─è│
#è 1 - (-4)è1 + 4è5è│ë 5y - 15 = x -1ë┌─¥ï-x + 5y = 14
êêêë │ -x + 5y - 15 = -1ê│ëx - 5y = -14
êêêë │ë -x + 5y = -1 + 15ï┘
Ç A
14ïFind the equation in standard form of the line passing
êëthrough (5,-4) and (-6,-3).
êêêêêêêêêïå
ïA)ï5x - 4y = 6ëB)ïx + 11y = -39è C) 6x + 3y = 11è D)ïof
êêêêêêêêêïç
üêêê │êêè1
êêêê│èy - (-4) = - ──(x - 5)
è -3 - (-4)ï-3 + 4è 1ï│êêï11
m = ──────── = ────── = ─── │
#ë-6 - 5ë-11ë-11 │ë11y + 44 = -x + 5è┌─¥ïx + 11y = -39
êêêê│ x + 11y + 44 = -1ê│
êêêê│ë x + 11y = 5 - 44è┘
Ç B